2022
DOI: 10.1002/advs.202200079
|View full text |Cite|
|
Sign up to set email alerts
|

Transporting Hydrogel via Chinese Acupuncture Needles for Lesion Positioning Therapy

Abstract: Lesion positioning therapy optimizes medical treatment by directly targeting lesions. However, strong physical barriers greatly hinder its wide use. Here, the Chinese acupuncture needles (CA‐needles) with a screw‐thread structure at the tip (ST‐needle) and the hydrogel with the function of adhesive metal and loaded drug sustained‐release structure are designed, through the minimally invasive and precise positioning of lesions by ST‐needles, the dry‐wet conversion of hydrogel with absorbing fluids and swelling,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Studies proved that Baicalein, as a flavonoid drug, possesses effective antioxidant property [28,65]. In Fig.…”
Section: Antioxidant Activitymentioning
confidence: 96%
See 1 more Smart Citation
“…Studies proved that Baicalein, as a flavonoid drug, possesses effective antioxidant property [28,65]. In Fig.…”
Section: Antioxidant Activitymentioning
confidence: 96%
“…Baicalein, the main bioactive flavone of Scutellaria baicalensis Georgi, has been proven that possesses excellent antibacterial, anti-inflammatory, and antioxidative properties [28,65].…”
Section: In Vitro Baicalein Releasementioning
confidence: 99%
“…Therefore, the way in which hydrogels can be safely and effectively delivered into IVDs is a challenge. Lin et al 184 punctured the articular cartilage with a special Chinese acupuncture needle to deliver the hydrogel to the lesion, and the micropores left by the acupuncture needle promoted the migration of stem cells. This study revealed that we can deliver the hydrogel into the IVD by penetrating the cartilage endplate through the vertebral body or pedicle with a special needle, and at the same time, the hole generated by the needle would promote the migration of BMSCs in the vertebrae of the IVD, which may be a direction for our future research.…”
Section: Problems and Challengesmentioning
confidence: 99%
“…In addition, inevitably intraoperative loss of healthy tissues in the tumor resection area is difficult to self-heal, which seriously affects the appearance, function, and life quality of patients [12,13]. To overcome these limitations, implant scaffold-based drug delivery systems, including films, hydrogels, and fibers, have been employed for improving chemotherapy efficacy, reducing toxicity and side effect, and repairing the healthy tissues [14][15][16][17][18][19][20][21]. Unfortunately, the postoperative chemotherapy and repair processes are hardly realized synchronously, which are commonly carried out in a separate way, resulting in low efficiency and cost.…”
Section: Introductionmentioning
confidence: 99%